Detection of Flavonoids from Acalypha indica L. - Narwade, V T; Waghmare, A A; Vaidya, A L (Journal of Ecobiotechnology, 2012)
Flavonoids from Acalypha indica L were extracted by using different solvent and they were identified and detected by Paper Chromatography (PC) and spectroscopic method. Flavonoids like anthocyanidins, glycosides, flavonols and flavones were detected from A. indica L.